Analisis Implementasi Online Food Delivery (OFD) Sebagai Strategi Pemasaran Digital di Food Court Tjendana Food Point - R. Dewi Sulastriningsih; Srie Wijaya Kesuma Dewi; Yunika Komalasari; Phitsa Mauliana; Ricky Firmansyah; Nanang Hunaifi (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The culinary business experiences continuous growth, the number of culinary businesses that keep popping up. The trigger for the growth of the culinary business is the presence of various online promotional media, including online food delivery. The purpose of this research is to analyze internal and external factors in online marketing using OFD MSME food at Tjendana Food Point. The method used is descriptive qualitative method. Data validity tests were carried out, namely data reduction, triangulation, and data display. The results of the study show that ordering food through OFD increases during Covid-19, the holiday season, and when OFD applicators apply promos. Apart from these moments, ordering food through OFD seemed normal. Apart from serving food delivery, OFD has also become a trend in modern society, which is a way to order food using a smartphone through an OFD provider application. For business actors, the presence of OFD is an alternative to being able to open a food business even if they do not have a shop or restaurant or when the place of business is not possible to receive guests. In addition to the perceived benefits, business actors, customers and driver-partners also feel that the tariffs applied by OFD applicators make prices high for customers but income for business actors and drivers tends to be minimal.